Fabricação de dispositivos nanoeletrônicos baseados em nanotubos de carbono - Indhira Oliveira Maciel (2015)
I this work we implement nano-fabrication techniques to construct and make measurements in single-walled carbon nanotubes (SWNTs) based devices. The nanotubes used were grown by CVD (chemical vapour deposition) method onto silicon dioxide surface and by HipCO (high pressure carbon monoxide convertion) method. The further were used in aqueous suspention using surfactants. We studied the suspended SWNTs deposition in a chemically functionalised silicon dioxide substrate by a self-assembled -NH2 terminated monolayer. We have studied the effects of time of deposition and suspention concentration on the prepared samples using SPM (scanning probe microscopy) method. Once we had the isolated SWNTs onto the silicon dioxide substrate, we have made lithographic marks using optical and electron-beam lithographies to index the tubes onto the surface using SPM method. Metallic contacts were then fabricated combining the two lithographic methods mentioned above to contact the ends of the tubes to perform electrical transport measurements.